PAEDAGOGIC COMPETENCY STRENGTHENING TEACHERS OF VOCATIONAL SCHOOLS OF WIDYA PRAJA UNGARAN THROUGH TRAINING OF LEARNING MODELS - Setiyani, Rediana; Nuryana, Ita; Tarmudji, Tarsis (Universitas Negeri Semarang, 2019)
Entering the industrial era 4.0, the challenges of life and life are very dynamic and complex. All want a fundamental and significant change in the process of education and learning of students, which contains strong implications for changes in the roles and tasks performed by teachers.Pedagogic competence is one of the competencies that must be mastered by a teacher. Teachers can develop their competencies through learning from various training programs from schools and from outside the school and from school infrastructure, libraries, laboratories, internet, as well as other educational programs and facilities. Thus, teachers are expected to be able to be professional in the education and teaching process in the classroom. Schools are expected to provide training and learning resources for the formation of competent teachers, schools are expected to have a teacher competency development management. One of the competencies that must be possessed by a teacher is pedagogical competence. From the results of UKG in the city of Semarang many teachers did not qualify. The UKG results for pedagogical competencies alone, the average national score in 2015 was only 48.94, which is far below the minimum competency standard (SKM), which is 55. And in 2016, the national pedagogic average increased to 63, 79 However, this figure is still below the 2016 Minimum Competency Standard (SKM) of 65. For this reason, efforts need to be made to strengthen teacher pedagogical competence. The community service team of Economic Education, UNNES Faculty of Economics held a training learning model to strengthen the pedagogical competence of Widya Praja Ungaran vocational school teachers. Memasuki era industri 4.0, tantangan hidup dan kehidupan sangatlah dinamis dan kompleks. Semua menghendaki adanya perubahan yang mendasar dan signifikan terhadap proses pendidikan dan pembelajaran peserta didik, yang di dalamnya mengandung implikasi kuat terhadap perubahan peran dan tugas yang dilakukan oleh guru. Kompetensi Pedagogik merupakan salah satu kompetensi yang harus dikuasi oleh seorang guru. Guru dapat mengembangkan kompetensinya melalui belajar dari berbagai program latihan dari sekolah maupun dari luar sekolah dan dari sarana prasarana (perpustakaan, laboratorium, internet) sekolah, serta program dan fasilitas pendidikan lainnya. Dengan demikian, diharapkan guru akan mampu bersikap profesional dalam proses pendidikan dan pengajaran di kelas. Sekolah diharapkan menyediakan pelatihan dan sumber belajar demi terbentuknya guru yang kompeten, sekolah diharapkan memiliki manajemen pengembangan kompetensi guru. Salah satu kompetensi yang harus dimiliki seorang guru adalah kompetensi pedagogik. Dari hasil UKG di kota Semarang banyak guru-guru yang tidak lolos. Hasil UKG untuk kompetensi bidang pedagogik saja, rata-rata nilai nasional tahun 2015 hanya 48,94, yakni berada jauh di bawah standar kompetensi minimal (SKM), yaitu 55. Dan pada tahun 2016, rata-rata pedagogik nasional mengalami peningkatan menjadi 63,79. Namun, angka ini masih di bawah Standar Kompetensi Minimal (SKM) 2016 sebesar 65. Untuk itu, perlu dilakukan upaya untuk memperkuat kompetensi pedagogik guru. Tim pengabdian kepada masyarakat Pendidikan Ekonomi, Fakultas Ekonomi UNNES mengadakan pelatihan model pembelajaran untuk menguatkan kompetensi pedagogik guru SMK Widya Praja Ungaran.